SAGE qualitative research methods - Atkinson, Paul, 1947-; Delamont, Sara, 1947- (London : SAGE, 2010)
SAGE has been a major force shaping the field of qualitative methods. This collection includes research from the past four decades and addresses key issues or controversies, such as explanations and defences of qualitative methods, ethics research questions and foreshadowed problems, access, and first days in the field.
"SAGE research methods online."
Title from home page (viewed Nov. 26, 2010).
Includes bibliographical references and index.
Specialized.
Also issued in print format.
Mode of access: World Wide Web.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology; Qualitative research